The actual challenges for energy monitoring at the municipal facilities - Kotsar, O.; Karpenko, A. (Energy and Automation, 2025)
The balanced use of energy resources and the reduction of harmful emissions are an integral part of the urgent tasks of state administration and local self-government for the sake of sustainable development of communities. Achieving these goals is impossible without the use of highly efficient energy management systems which based on productively energy monitoring systems. However, research results indicate the presence of critical problems in the functioning of such systems in municipalities, which renders the entire process of community energy management ineffective. The paper analyzes the results of the implementation and application of energy monitoring systems in municipalities and territorial communities of Ukraine within the framework of the valid legislative and regulatory frameworks, performs a gap-analysis of the regulatory framework for ensuring the functioning of energy monitoring systems in municipalities, identifies the factors and causes of the ineffectiveness of such systems, and suggests ways to overcome them. The main focus is on improving legislative and regulatory support for procedures for collecting and analyzing data on energy use. Research results prove that ensuring the reliability and relevance of data provided by high-performance energy monitoring systems contributes to the development of local autonomy, supports communications and cooperation between parties, and motivates productive actions. It also helps to effectively distribute energy efficiency improvement tasks between different levels of management.Key words: energy efficiency, energy management, energy monitoring, EnMS, energy monitoring system, energy efficient municipality